Development of Visual EMU, a graphical user interface for the peridynamic EMU code - Birkey, Justin (Kansas State University, 2007)
This thesis provides a description of Visual EMU, a graphical user interface for the peridynamic EMU code. The peridynamic model is a fundamental method for computational mechanical analysis that makes no assumption of continuous or small deformation behavior and has no requirement for the concepts of stress and strain. The model does not require spatial derivatives and instead uses integral equations. A force density function, called the pairwise force function, is postulated to act between each pair of infinitesimally small particles if the particles are closer together than some finite distance. A spatial integration process is employed to determine the total force acting upon each particle and a time integration process is employed to track the positions of the particles due to the applied body forces and applied displacements. EMU is a computer code developed by Sandia National Laboratories that implements the peridynamic model. Visual EMU is a pre-processor for the EMU code that allows any user to enter all parameters and visualize the resulting material regions, peridynamic grid, and a preview of resulting nodes. Visual EMU can be used before starting a lengthy solution with potential errors. The language, visual layout, and code design of Visual EMU are described along with two examples and their results.
Keywords: peridynamics; emu; visual emu; gui; model; Engineering, Mechanical (0548)